2011
DOI: 10.1371/journal.pone.0022988
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miRNA as Biomarkers for Assessment of Total-Body Radiation Exposure Dosimetry

Abstract: The risk of radiation exposure, due to accidental or malicious release of ionizing radiation, is a major public health concern. Biomarkers that can rapidly identify severely-irradiated individuals requiring prompt medical treatment in mass-casualty incidents are urgently needed. Stable blood or plasma-based biomarkers are attractive because of the ease for sample collection. We tested the hypothesis that plasma miRNA expression profiles can accurately reflect prior radiation exposure. We demonstrated using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 49 publications
6
73
1
1
Order By: Relevance
“…These findings demonstrate that the Arabidopsis spike-ins represent effective experimental controls for the analysis of endogenous human miRNA expression when performing the short RNA enrichment procedure. Interestingly, Cui et al (38) showed that miR-159a also serves as an effective spike-in control for RNA extraction of plasma samples, demonstrating its general suitability for RNA isolation procedures. Other previous studies have also assessed the use of other non-mammalian spike-in miRNAs to control for technical variability associated with the entire RNA extraction process (8, 32, 36, 37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrate that the Arabidopsis spike-ins represent effective experimental controls for the analysis of endogenous human miRNA expression when performing the short RNA enrichment procedure. Interestingly, Cui et al (38) showed that miR-159a also serves as an effective spike-in control for RNA extraction of plasma samples, demonstrating its general suitability for RNA isolation procedures. Other previous studies have also assessed the use of other non-mammalian spike-in miRNAs to control for technical variability associated with the entire RNA extraction process (8, 32, 36, 37).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further work is required to optimize the usage of miRNA spike-ins to control for technical variability in total RNA isolation and short RNA enrichment procedures, including the establishment of the most effective methods of sample normalization and the most suitable number of spike-in miRNAs to use. For example, whereas Kroh et al (37) and Mitchell et al (8) used multiple spike-in miRNAs, other researchers have used single spikes (32, 38). …”
Section: Resultsmentioning
confidence: 99%
“…The extracellular miRNAs that can function in recipient cells are named as shuttle miRNAs, it may convey specific information from its donor cells to other recipient cells and hence plays various physiological functions. Recent studies have suggested that the expressions of specific miRNAs in blood plasma could be used as biomarkers of radiation dosimetry [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Humans belong to the animals with lowest resistance, with an estimate for the LD 50 range of 3.5 to 4.5 Gy (Gray) (Cui et al, 2011). For some other animals the corresponding values are: monkey 4.5 Gy, mouse 4.5 Gy, rat 6 Gy, goldfish 7.5 Gy, rabbit 8 Gy, and cockroach 50 Gy (Bolus, 2001).…”
Section: Introductionmentioning
confidence: 99%